Deconstructing epidemiology - Rohina Joshi; Rohit Joshi (Wolters Kluwer Medknow Publications, 2015)
Epidemiology is defined as "the study of the distribution and determinants of health-related states or events (including disease) in specified populations and the application of this study to control health problems." This article gives an overview and an introduction to epidemiology and explains the main study designs. The article also discusses the key ethical issues in epidemiological studies and its applications to modern day medicine.